2013
DOI: 10.1021/cr300176g
|View full text |Cite
|
Sign up to set email alerts
|

Arylglyoxals in Synthesis of Heterocyclic Compounds

Abstract: ZIRAK, M.; AKBARI, A.; Chem. Rev. (Washington, DC, U. S.) 113 (2013) 5, 2958-3043, http://dx.doi.org/10.1021/cr300176g ; Dep. Chem., Fac. Sci., Univ. Maragheh, Golshahr, Maragheh, Iran; Eng.) -Lindner 27-219

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
192
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 379 publications
(192 citation statements)
references
References 1,693 publications
(759 reference statements)
0
192
0
Order By: Relevance
“…Exposure to pyridine has harmful effects on the liver, kidneys, immune systems and reproductive functions, and has potential carcinogenicity. [27][28][29][30][31] Following to recent reports about the application of arylglyoxals (AG) in heterocyclic chemistry, 26,[32][33][34][35][36][37][38][39][40] herein we have applied ZrOCl2•8H2O as recyclable, non-toxic and green catalyst for the regioselective synthesis of 3-arylpyrimido [4,5-c] We also studied the influence of the amount of ZrOCl2•8H2O on the reaction yields. We found that the best yield is obtained when we used the ZrOCl2•8H2O 20 mol% as a catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to pyridine has harmful effects on the liver, kidneys, immune systems and reproductive functions, and has potential carcinogenicity. [27][28][29][30][31] Following to recent reports about the application of arylglyoxals (AG) in heterocyclic chemistry, 26,[32][33][34][35][36][37][38][39][40] herein we have applied ZrOCl2•8H2O as recyclable, non-toxic and green catalyst for the regioselective synthesis of 3-arylpyrimido [4,5-c] We also studied the influence of the amount of ZrOCl2•8H2O on the reaction yields. We found that the best yield is obtained when we used the ZrOCl2•8H2O 20 mol% as a catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Also, it must be noted that 1,5-diarylhydantoins (2b) had also been prepared by arylglyoxals condensation with Narylureas in the presence of hydrochloric acid and acetic acid in boiling ethanol for 4 h. 6 It is obviously that 1-aryl-5-arylthiohydantoins formation from arylglyoxals hydrates and thiourea takes place in the presence of strong acid [3][4][5] or in boiling acetic acid solution. 2 But the course of this reaction in acetic acid media at room temperatures has not been studied.…”
Section: Methodsmentioning
confidence: 99%
“…A structure of compound 1a is consistent with data of 1 H and 13 C NMR spectra and mass-spectrum. 2 Also, it was shown that phenylglyoxal hydrate condensed with N-arylthioureas and N-arylureas yielding 1-aryl-5-phenylthiohydantoins (2a) and 1-aryl-5-phenylhydantoins (2b) (1,5-diarylimidazolidine-2,4-diones), 3,4 respectively, in the presence of polyphosphoric acid at microwave irradiation in the absence of solvent (Scheme 1). But this method needs using of large amounts of polyphosphoric acid (or "polyphosphoric ester"…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[38] It is known that poly(N-isopropylacrylamide) (PNIPAM) is one of the most important water-soluble polymers, which exhibits a heat-induced phase transition from coiled to globular state in an aqueous solution in response to temperature changes across a lower critical solution temperature (LCST) at 32°C, [39] by expanded conformation in water below the LCST due to strong hydration, and changes to compact forms above the LCST by dehydration. [40,41] Continuing our works on heterocyclic chemistry, [42][43][44][45] herein, we wish to report a new heterocyclic pH-responsive dye based on diazenylphenyl-1,3,4-oxadiazol moiety and its use in a novel water-soluble polymeric sensor, which responds to both pH and temperature.…”
Section: Introductionmentioning
confidence: 99%